THE EFFECTIVENESS OF PEN PAL PROJECT IN WRITING RECOUNT TEXT IN SMP DHARMA BAKTI MEDAN - Kardo Sihaloho; Sadariah Ujung; Fitri Dairina Berutu (Jurnal Education and Development, 2021)
This research describe the effectiveness of pen pal project, to find out students’ responses used new strategy especially for writing recount text skills in SMP Dharma Bakti Medan. And also how to prepare all the students to learn recount text topic with implementation of pen pal project. The researcher used seven grade students in SMP Dharma Bakti Medan as the subject of research with 30 participants. Research method that used by the researcher is qualitative-descriptive. Observation sheet along teaching and learning process is usefull for the researcher to observe pen pal project aplication by teacher to all the participants. The result of this research showed that pen pal project was effectived to increase students’ writing ability. Students more active to write after exchanging the letter to their friends or their family. In the last meeting students answered some questions about implementation of pen pal project and they interested to write recount text after send the letter. They agree that pen pal project prepared them to study about recount text topic.Based on the research, pen pal project can be a solution and motivation for teacher and students to create effective learning process. Improve students’ writing skills without trapped in stucture and vocabulary dificulties. The researcher expected the result of this study give some benefit for teachers, students and the others reseachers